Experimental investigation of surface roughness effect on fatigue performance of AISI 1045 carbon steel and fatigue limit prediction (Fracture and Structural Integrity, 2019)
In fatigue life, surface integrity perform a major role to determine the fatigue lifetime. It could differ greatly among specific cases even for the same solicitations. Indeed, the manufacturing process carries modifications on surface state, residual stresses and the microstructure which affects the fatigue behavior of mechanical parts.This article investigate the effect of surface roughness on the fatigue strength of AISI 1045 carbon steel obtained by the turning process. The work carried out consists in testing in uniaxial fatigue different batches of specimens which have a controlled surface state. The S-N curves obtained present a strong dependence between fatigue performance and surface state. Based on the surface topography, a model for predicting fatigue limit will be adopted.
Keywords: Fatigue; Surface roughness; Cutting condition; fatigue limit